Analysis of Endocannabinoid System in Rat Testis During the First Spermatogenetic Wave - Migliaccio, Marina; Ricci, Giulia; Suglia, Antonio; Manfrevola, Francesco; Mackie, Ken; Fasano, Silvia; Pierantoni, Riccardo; Chioccarelli, Teresa; Cobellis, Gilda (Frontiers in Endocrinology, 2018)
Endocannabinoids are lipid mediators, enzymatically synthesized and hydrolyzed, that bind cannabinoid receptors. Together with their receptors and metabolic enzymes, they form the “endocannabinoid system” (ECS). Anandamide (AEA) and 2-arachidonoylglycerol (2-AG) are the main endocannabinoids studied in testis. In this study, using the first wave of spermatogenesis as an in vivo model to verify the progressive appearance of germ cells in seminiferous tubules [i.e., spermatogonia, spermatocytes, and spermatids], we analyzed the expression of the main enzymes and receptors of ECS in rat testis. In particular, the expression profile of the main enzymes metabolizing AEA and 2-AG as well as the expression of cannabinoid receptors, such as CB1 and CB2, and specific markers of mitotic, meiotic, and post-meiotic germ cell appearance or activities have been analyzed by RT-PCR and appropriately correlated. Our aim was to envisage a relationship between expression of ECS components and temporal profile of germ cell appearance or activity as well as among ECS components. Results show that expression of ECS components is related to germ cell progression. In particular, CB2 and 2-AG appear to be related to mitotic/meiotic stages, while CB1 and AEA appear to be related to spermatogonia stem cells activity and spermatids appearance, respectively. Our data also suggest that a functional interaction among ECS components occurs in the testis. Indeed, in vitro-incubated testis show that AEA-CB2 activity affects negatively monoacylglycerol-lipase levels via upregulation of CB1 suggesting a CB1/CB2-mediated relationship between AEA and 2-AG. Finally, we provide the first evidence that CB1 is present in fetal gonocytes, during mitotic arrest.